Geology of Monte Gallo (Palermo Mts, NW Sicily). Issue 5 (19th October 2016) - Basilone, Luca; Di Maggio, Cipriano
ABSTRACT: The promontory of Monte Gallo (Palermo, NW Sicily) is a spectacular site where Upper Triassic-Eocene carbonate platform rocks and Quaternary continental to marine deposits are well exposed. A Mesozoic-Paleogene rock succession allows the potential visitor to easily detect the features and the evolution of the Panormide carbonate platform, a shallow-water paleogeographic domain of the Southern Tethyan margin. Quaternary deposits, as well many landforms, enable the visitor to directly identify the interplay between climate changes, tectonics and fluctuations of marine level that occurred during the Quaternary Period. A detailed geological map (1:15, 000 mapping scale) is presented, accompanied by a stratigraphic correlation of logged sections and morpho-stratigraphic and tectonic schemes of the area, aimed at highlighting the geological heritage of Monte Gallo in support of the establishment of a Geosite. The Geological Map and relevant explanatory notes should be used as cartographic support and as a field trip guide for possible geological itineraries.